2006
DOI: 10.1177/000348940611500906
|View full text |Cite
|
Sign up to set email alerts
|

Headache with Unilateral Pulsatile Tinnitus in Women Can Signal Dural Sinus Thrombosis

Abstract: It is important to be vigilant for the possibility of sigmoid sinus thrombosis in women who complain of unilateral head pain or unilateral pulsatile tinnitus. Appropriate imaging must be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Some studies reported that PT is associated with abnormal hemodynamics [2][3][4][17][18][19]. Consistent with previous studies, our results showed that SPD causing PT usually occurred on the dominant side of the venous outflow, which suggested PT's generation might require large blood flow.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies reported that PT is associated with abnormal hemodynamics [2][3][4][17][18][19]. Consistent with previous studies, our results showed that SPD causing PT usually occurred on the dominant side of the venous outflow, which suggested PT's generation might require large blood flow.…”
Section: Discussionsupporting
confidence: 90%
“…82 Typically, anticoagulation results in resolution of PT over several months as the thrombus resolves, with endovascular thrombectomy or decompressive surgery indicated in patients with acute presentation of severe disease. 80,82,83…”
Section: Dural Venous Sinus Thrombosismentioning
confidence: 99%
“…13 Patients presenting with the combination of PT and occipital headache are most concerning for carotid artery dissection [14][15][16] or dural AVF. 17,18 CNP with or without other focal neurological signs in patients complaining of PT may be due to intracranial hemorrhage or progressive MS. 19 A history of trauma is important as tinnitus resulting from head or neck injuries tends to be more severe than that from other causes. 12 Moreover, fatal causes of posttraumatic dural AVF have been reported, 20 thus, injury-related PT can be a sign of potentially lethal conditions.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…22 A traumatic carotid cavernous fistula is seen in 3.8% of traumatic skull base fractures. 18 Patient age is also important as studies demonstrate that the age of PT with AV fistula is common between the age of 30 and 45 years, 23,24 and DA of internal carotid artery has a peak incidence in the fourth decade. 25 Furthermore, the age of PT with arterial hypertension and vascular stenosis usually develops between the age 45 and 60 years, becoming more prevalent in older individuals.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%